Lifelong Physical Activity Regardless of Dose Is Not Associated With Myocardial Fibrosis. (November 2016) - Abdullah, Shuaib M.; Barkley, Kyler W.; Bhella, Paul S.; Hastings, Jeffrey L.; Matulevicius, Susan; Fujimoto, Naoki; Shibata, Shigeki; Carrick-Ranson, Graeme; Palmer, M. Dean; Gandhi, Nainesh; DeFina, Laura F.; Levine, Benjamin D.
Abstract : Background—: Recent reports have suggested that long-term, intensive physical training may be associated with adverse cardiovascular effects, including the development of myocardial fibrosis. However, the dose–response association of different levels of lifelong physical activity on myocardial fibrosis has not been evaluated. Methods and Results—: Seniors free of major chronic illnesses were recruited from predefined populations based on the consistent documentation of stable physical activity over >25 years and were classified into 4 groups by the number of sessions/week of aerobic activities ≥30 minutes: sedentary (group 1), <2 sessions; casual (group 2), 2 to 3 sessions; committed (group 3), 4 to 5 sessions; and Masters athletes (group 4), 6 to 7 sessions plus regular competitions. All subjects underwent cardiopulmonary exercise testing and cardiac magnetic resonance imaging, including late gadolinium enhancement assessment of fibrosis. Ninety-two subjects (mean age 69 years, 27% women) were enrolled. No significant differences in age or sex were seen between groups. Median peak oxygen uptake was 25, 26, 32, and 40 mL/kg/min for groups 1, 2, 3, and 4, respectively. Cardiac magnetic resonance imaging demonstrated increasing left ventricular end-diastolic volumes, end-systolic volumes, stroke volumes, and masses with increasing doses of lifelong physical activity. One subject in group 2 had late gadolinium enhancement in a noncoronary distribution, and no subjects in groups 3 and 4 had evidence of late gadolinium enhancement. Conclusions—: A lifelong history of consistent physical activity, regardless of dose ranging from sedentary to competitive marathon running, was not associated with the development of focal myocardial fibrosis.